This **preview** has intentionally **blurred** parts. Sign up to view the full document

**Unformatted Document Excerpt**

When using the product rule, if the bases are the same then one would keep the base and add the exponents together. EXAMPLE: 6 3 x6 4 = 6 3+4 = 6 7 When raising a product to a power, one needs to raise each factor to the power of exponents. EXAMPLE: (xy) 3 = x 3 y 3 The negative exponents rule is difficult for me to explain, but as I understand it, one takes the reciprocal of the base. EXAMPLE: 4-2 = 1 or 1 = 4 2 4 2 4-2 Expression using scientific notation: 1 answer : 1 x 10-10 or 0.0000000001 10 10... View Full Document